International Financial Statistics Supplement on International Reserves. (International Financial Statistics; Volume *, ;, 1983)
This paper presents the Supplement on international reserves, the sixth in the series of supplements to International Financial Statistics (IFS) that comprises textual material commencing with an historical perspective of international reserves. This is followed by a discussion on the methodology covering the concepts underlying the reserves data in IFS: the data collection and presentation procedures; the related data in the money and banking, and balance-of-payments sections in IFS; and a summary of the national concepts of reserves. Statistics on international reserves are important indicators of the external economic performance of countries. A country's holdings of international reserves represent its ability to meet balance of payments needs through official financial settlements. The establishment of the IMF led to the creation of a reserve asset in the form of a gold tranche position reflecting a member's subscription to the IMF in gold. To the extent that the IMF made use of a member's currency in drawings of other countries, a creation of new reserves was involved.